2015
DOI: 10.1596/978-1-4648-0706-0
|View full text |Cite
|
Sign up to set email alerts
|

Learning in the Face of Adversity: The UNRWA Education Program for Palestine Refugees

Abstract: Some rights reserved 1 2 3 4 18 17 16 15 World Bank Studies are published to communicate the results of the Bank's work to the development community with the least possible delay. The manuscript of this paper therefore has not been prepared in accordance with the procedures appropriate to formally edited texts. This work is a product of the staff of The World Bank with external contributions. The findings, interpretations, and conclusions expressed in this work do not necessarily reflect the views of The World… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A quasi-experimental study that examined the impact of a school program that sought to integrate drama, movement, music and art into primary schools in northern Uganda found statistically significant improvements in students' wellbeing (Ager et al, 2011). These findings are echoed in systematic reviews (see for example Tyrer & Fazel, 2014) and mixed methods research with Palestinian refugees (Abdul-Hamid et al, 2016). This evidence highlights the importance of child and youth-centered pedagogies and multi-faceted curricula.…”
Section: Enhancing the Protective Capacity Of Schools Through Interventions Focused On School Safety And Child And Youth Centered Instrucmentioning
confidence: 97%
“…A quasi-experimental study that examined the impact of a school program that sought to integrate drama, movement, music and art into primary schools in northern Uganda found statistically significant improvements in students' wellbeing (Ager et al, 2011). These findings are echoed in systematic reviews (see for example Tyrer & Fazel, 2014) and mixed methods research with Palestinian refugees (Abdul-Hamid et al, 2016). This evidence highlights the importance of child and youth-centered pedagogies and multi-faceted curricula.…”
Section: Enhancing the Protective Capacity Of Schools Through Interventions Focused On School Safety And Child And Youth Centered Instrucmentioning
confidence: 97%
“…However, we also identified one study that found that refugees outperformed their non-refugee peers. Using data from the PISA and TIMSS tests conducted in 2007, classroom observations, and interviews with students, the World Bank examined how Palestinian refugees attending UNRWA schools performed compared to their peers in public schools in Jordan, Gaza, and the West Bank (Abdul-Hamid, Patrinos, Reyes, Kelcey, & Diaz Varela, 2016). Findings showed that refugee students outperformed non-refugees by the equivalent of one year of schooling.…”
Section: Learning Outcomes For Migrantsmentioning
confidence: 99%
“…This paper grows out of the author's academic and professional work in the region, primarily with the United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA) (Abdul-Hamid et al 2015), explained later, with the British Council and universities in Jordan and West Bank. It is a preliminary work to scope out how research work might explore discrepancies between the digital environment,…”
Section: Introduction and Rationalementioning
confidence: 99%